Where Policy and Culture Collide: Perceptions and Responses of Swidden Farmers to the Burn Ban in West Kalimantan, Indonesia - Daeli, W.; Carmenta, R.; Monroe, M.C.; Adams, A.E. (Springer, 2021)
Catastrophic uncontrolled fires are a leading social-environmental challenge that now occur even in the humid tropics. In 2015 extensive Indonesian peatland fires commanded national and international attention and resulted in a ban on all burning in the country extending to traditional farmers practicing small-scale fire-based agriculture on mineral soils. However, the impacts of, and responses to the ban on these fire-dependent communities is not well understood. Understanding the mental models of communities exposed to environmental change and its corresponding policy responses can provide salient insights into the place-based experience of change to identify contested perceptions and serve to improve the distributional equity of associated impacts. We assessed the mental models of Dayak farmers in Kapuas Hulu, Kalimantan, in three distinct landscape contexts: i) oil palm (OP), ii) national park (NP), and iii) transition (T) sites. These locations enabled insights into how different contemporary landscape contexts and livelihood opportunities are related to experiences and coping strategies. We collected data using the Conceptual Content Cognitive Mapping approach in two communities in each landscape context (n = 24 participants per landscape), and 72 interviews in total. Results show that the NP and T sites were most similar, whilst the OP communities held distinct perceptions of fire. In addition to the agricultural value of fire, cultural and relational values are associated with fire use across sites and would be severed through fire prevention. Finally, we show that the burdens of the burn ban for farmers and forests were most pronounced in the NP and T sites where farmers are most reliant on traditional agriculture, have the fewest livelihood alternatives and least external support to fight uncontrolled fires.